Conceptual dimensions of social-psychological assistance to the population - Vasylkiv, Olena (Psyhology & society, 2019)
The article presents the results of a scientific search aimed at theoretical-critical comprehension of the essential content of socio-psychological assistance for personality. The research also presents significant differences between available in scientific discourses terms “social assistance”, “psychological assistance”, the clear delineation of concepts of “socio-psychological assistance” and “psychosocial assistance” and substantiates logical-content format of the correct use of the mentioned definitions. Based on the vita-cultural methodology of A. V. Furman and his scientific school, on the principles of quaternity, the conceptual dimensions of the socio-psychological assistance for personality are singled out and characterized: 1) socio-psychological assistance, 2) socio-psychological provision, 3) socio-psychological accompaniment, 4) socio-psychological protection, and also the main forms and methods of achieving socio-psychological well-being in the conditions of the uncertainty of the modern problem nowadays are outlined. In addition, the organic complementarity of the social and psychological dimensions of assistance for personality is logically argumented, that covering, on the one hand, the forms and directions of the functioning of the corresponding social structures (assistance, provision, accompaniment, protection; support, insurance, service, etc.), from another – forms, methods and directions of competent psychological work (psychological assistance, support, accompaniment, help; psycho-diagnosis, psycho-counseling, psychotherapy, psycho-correction, psycho-rehabilitation, etc.).